Design And Development Of Sales E-Monitoring Information System Case Study : PT. Pratama Inti Distribusindo - Nicken Litan Margareta; Amesanggeng Pataropura (Komunitas Dosen Indonesia, 2018)
We must recognize the development of technology at this time has developed very rapidly in this era of globalization. Moreover, the development of internet-based computer technology. By using the internet we can search for the information we need from around the world quickly and accurately. However, there are still many companies in Indonesia that have difficulty in implementing computerized systems within the company, especially in internet-based information systems. From the research conducted, there are several weaknesses in the processing of reports that occur, namely it takes a long time to make a form, record the transactions and also take a lot of paper / media recording. In addition, there is no computerized system dedicated to this process. With the creation of a system of making reports with this method, it is expected to assist in generating reports and checking jobs faster and more accurately. After the design, manufacture, and testing of the application application and inventory inventory program, conclusions can be drawn, namely more company performance efficient and prone to errors if data entry is incorrect. In implementing the new system, it is expected to run smoothly.